Implementation of multisource data fusion satellite embedded system based on array cluster clustering algorithm - Jiang, Xiaoyong; Liu, Liangfeng; Xi, Peili; Zhu, Xinzhong; You, Yuehui; Lou, Yutao; Yang, Yong (Proceedings of SPIE, the international society for optical engineering, 2025)
At present, single satellite target detection, extraction, and tracking have gradually matured, but multi satellite collaborative fusion is still in the development stage. With the increase in the number of satellites and the completeness of satellite types, higher requirements have been put forward for the fusion of multi-source data from multiple satellites on board. This article proposes a satellite based multi-source data fusion system based on array clustering algorithm. Taking advantage of the poor absolute positioning accuracy of satellites for sea surface ship targets and the high relative positioning accuracy between ship targets, multiple satellites are matched and correlated frame by frame to form trajectories for target detection images in the region, achieving the goal of multi satellite data fusion. This algorithm relies solely on point position information fusion and does not depend on specific satellites, making it suitable for constellation level multi-source data fusion. To meet the needs of localization, this algorithm is based on Ascend310 to achieve multi-source data fusion on board the satellite. The external information flow interface design meets the requirements of the entire satellite information flow and has been verified in orbit.